Case report: Diagnostic challenges in a patient with alcohol use disorder that developed following a stroke - Zeitlin, Jacob; Kotbi, Nabil (Frontiers in Psychiatry, 2023)
Patients with comorbid neurological and psychiatric diseases often face considerable impairment, causing challenges that pervade many aspects of their lives. Symptoms can be especially taxing when one or more of these conditions is severely disabling, as the resulting disability can make it more challenging to address comorbidities. For clinicians, such patients can be quite difficult to both diagnose and treat given the immense potential for overlap between the underlying psychiatric and neurologic causes of their symptoms—as well as the degree to which they might exacerbate or, conversely, mask one another. These intricate relationships can also obscure the workup of more acute pathologies, such as alcohol withdrawal and delirium. This report details the complex history and clinical challenges in a 54-year-old man who was no longer able to work after developing multiple neurologic deficits from a left MCA stroke a decade earlier. The intellectual and motor disabilities he faced in the aftermath of his stroke were subsequently compounded by a steady increase in alcohol consumption, with his behavior ultimately progressing to severe alcohol use disorder. The coinciding neurologic and psychiatric manifestations obfuscate the workup—and therefore the management—of his major depressive disorder. In pursuit of the optimal approach to address these comorbid conditions and promote recovery, an investigation into possible mechanisms by which they are interconnected revealed several potential neuropsychiatric explanations that suggest targets for future therapeutic strategies.